1994
DOI: 10.1161/01.cir.89.1.76
|View full text |Cite
|
Sign up to set email alerts
|

Abrupt complement activation and transient neutropenia in patients with acute myocardial infarction treated with streptokinase.

Abstract: Streptokinase treatment of AMI causes abrupt activation of the complement system, whereas no significant complement activation can be detected in plasma of AMI patients not treated with fibrinolytic agents. Complement activation causes a transient leukopenia, as reported for such other clinical conditions as dialysis and cardiopulmonary bypass, and possibly contributes to the hypotension observed during streptokinase treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…This raises the question as to whether the low plasma sCR1 could be entirely because of streptokinase therapy. Although such a possibility cannot be completely ruled out, it appears unlikely because complement activation after thrombolytic therapy is abrupt and settles by 24 h after infusion of streptokinase [14]. In our patients, the sCR1 levels continued to be significantly below normal even at the time of discharge from hospital and therefore appear to be independent of any direct action of the streptokinase infusion.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…This raises the question as to whether the low plasma sCR1 could be entirely because of streptokinase therapy. Although such a possibility cannot be completely ruled out, it appears unlikely because complement activation after thrombolytic therapy is abrupt and settles by 24 h after infusion of streptokinase [14]. In our patients, the sCR1 levels continued to be significantly below normal even at the time of discharge from hospital and therefore appear to be independent of any direct action of the streptokinase infusion.…”
Section: Discussionmentioning
confidence: 55%
“…Studies have shown that streptokinase therapy per se is associated with complement activation [14,15]. We did not study patients with acute myocardial infarction who did not receive thrombolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Hypotension is a well-known and well-described side effect of SK (9,11). It has been demonstrated that treatment with SK in itself causes hypotension as compared to in patients with AM1 not treated with SK (7). The hypotension has been attributed to the rate of infusion of SK, for which reason a rate of infusion less than 500 U kg-' min-' has been re-Received November 5, 1996.…”
mentioning
confidence: 99%
“…Other post-ischemic microvascular alterations such as increased adhesiveness of PMNs to endothelial cells and reduced myocardial perfusion pressure compound the problem of regional plugging of microvessels. Upon reperfusion, marked complement activation and generation of chemotactic activity capable of priming PMNs have been observed [3][4][5]. Activated PMNs release proteinases, OFRs, and other pro-inflammatory mediators which can cause direct tissue injury.…”
Section: Discussionmentioning
confidence: 99%